Synthesis, Characterization and Biological Properties of Ruthenium(III) Complexes - Sampath, K.; Azarudeen, R.; Sathiyara, S.; ayabalakrishnan, C. (University of Jaffna, 2019)
The ruthenium complexes were synthesized from ruthenium(III) metal precursors and thiosemicarbazone ligands by ligand exchange reactions. The structural features of the synthesized complexes were studied by various physico-chemical and spectroscopic techniques. In all the complexes studied, the Schiff bases act as bidentate ligands. The efficiency of the ruthenium(III) complexes towards the biomolecules, the interaction between DNA/BSA was studied. In addition, the cytotoxic properties of the complexes were evaluated against a panel of bacteria and the efficiency of complexes to arrest the growth of HeLa and MCF-7 tumour cell lines have been studied along with cell viability test under in vitro conditions. The results showed a dose dependent anti-proliferative effect, thus indicating the biological significance of the complexes. Moreover, the complexes were examined the oxidation inhibition property against the DPPH and OH radicals.